Assessment of pre- and post-harvest losses of vegetables in Kanpur district of Uttar Pradesh (Current Horticulture, 2024)
The study was carried out to find out pre and post-harvest losses in vegetable, viz. tomato (Solanum lycopersicum L.), brinjal (Solanum melongena L.), okra (Abelmoschus esculentus L.), cauliflower (Brassica oleracea var. botrytis) and bottle gourd (Lagenaria siceraria) in Kanpur district of Uttar Pradesh, during 2017-18. Multistage sampling was done for selection of 100 vegetable growers. The sample also included 30 market functionaries. The maximum aggregate losses was found in tomato, followed by brinjal, cauliflower, bottlegourd and okra. The pre-harvest losses at farmers' level contributed for more than 40% of the total losses at farmers' level in all vegetables except cauliflower. The study has recommended that establishment of producer co-operatives to handle various activities relating to production and marketing of vegetables would help in reducing losses.
Keywords: Cooperatives; Farming level; Market functionaries; Multistage sampling; Post-harvest losses; Pre-harvest losses